Efektivitas Layanan Bimbingan Kelompok dengan Metode Think Pair Share terhadap Self Control Penggunaan Gadget - Angel Oktaviani; Donal Donal; Raja Arlizon (Departement of Mathematics Education, 2023)
This research is a quantitative research with an experimental research method using a Quanti Experimental Design with a Nonequivalent Control Group Design design in which there are two groups that are not randomly selected, in which the group taking the subject is selected using a probability sampling technique with a purposive sampling technique. The data collection was carried out through the distribution of pretest and posttest which were then analyzed using the Spearman rank test and Wilcoxon test with the help of the SPSS version 23 for windows application program to see how much influence and effectiveness of group guidance services with the think pair share method have on self-control of gadget use. Based on the results of the data obtained, there was an increase in self-control in the use of gadgets before and after being given group guidance services using the think pair share method in the experimental group and the control group. Then it was found that group guidance services using the think pair share method had an effect on self-control of gadget use by 63%. Furthermore, this study shows that group guidance services using the think pair share method are effective for increasing self-control in using gdgets.